Model-in-the-loop simulation of gap and torque tracking control using electronic wedge brake actuator. (1st January 2014) - Aparow, Vimal Rau; Hudha, Khisbullah; Ahmad, Fauzi; Jamaluddin, Hishamuddin
This paper presents gap and torque tracking controls of a new braking system for Brake-by-Wire (BBW) using a wedging mechanism. A validation technique known as Model-in-the-Loop Simulation (MILS) is proposed to evaluate the effectiveness of EWB actuator and model. MILS is divided into two types of techniques, which are Hardware-in-the-Loop Simulation (HILS) using real EWB actuator and Software-in-the-Loop Simulation (SILS) using Gaussian cumulative distribution technique. A brake test rig is developed for HILS using EWB actuator, Electronic Control Unit, National Instrument board, xPC Host and Target PC. Meanwhile, mathematical equations are developed for SILS using Matlab Simulink. Both techniques are used to evaluate the performance of EWB actuator and EWB's mathematical model in controlling the gap and torque using various inputs. The results show that the responses from the actuator and EWB model closely followed the desired trajectories, indicating that EWB is capable to be used for vehicle active braking.